Temporal and Spatial Variation in the Population Structure of Spanish Fusarium circinatum Infecting Pine Stands - David Fariña-Flores; Mónica Berbegal; Eugenia Iturritxa; Laura Hernandez-Escribano; Olga Aguín; Rosa Raposo (Journal of Fungi, 2023)
Fusarium circinatum is an introduced fungal pathogen extended to the northern regions of Spain that causes Pine Pitch Canker (PPC) disease. In this work, we analyzed the pathogen’s genetic diversity to study changes over time and space since the first outbreak occurred in Spain. Using six polymorphic SSR markers, 15 MLGs were identified in 66 isolates, and only three haplotypes were found with frequencies higher than one. In general, genotypic diversity was low and decreased shortly over time in the northwestern regions while maintained at País Vasco, where only one haplotype (MLG32) was detected 10 years. This population also included isolates of a single mating type (MAT-2) and VCGs identified in only two groups, while isolates from NW regions were of both mating types and VCGs represented in 11 groups. The existence of haplotype MLG32 maintained on time and widely distributed suggests its good adaptation to the environment and the host. Results showed that the pathogen in País Vasco remains clearly differentiated from other northwestern populations. This fact was supported with no evidence of migration among regions. Results are explained by the asexual reproduction, but also selfing at least to a lesser extent that leads to identification of two new haplotypes.